311 Phase II trial of lymphodepletion plus adoptive cell transfer with or without dendritic cell vaccination in patients with metastatic melanoma. (9th November 2020) - Saberian, Chantal; Amaria, Rodabe; Haymaker, Cara; Forget, Marie Andree; Bassett, Roland; Glitza, Isabella; Lizee, Gregory; Yee, Cassian; McQuade, Jeniffer; Wong, Michael; Tawbi, Hussein; Patel, Sapna; et al.
Abstract : Background: Adoptive cell therapy (ACT) using autologous tumor-infiltrating lymphocytes (TIL) has shown great benefit in patients with melanoma. 1, 2 It was suggested that long term tumor immunosurveillance is provided by TIL persisting after transfer. Dendritic cells (DC) are professional antigen presenting cells and have the ability to optimally activate T lymphocytes. 3 We hypothesized that the combination of autologous TIL containing a population of HLA-A0201 restricted MART-1 reactive CD8+ TIL with autologous MART-1 antigen-pulsed DCs will result in enhanced proliferation and prolonged survival of the transferred antigen-specific T cells in vivo, thus leading to improved clinical responses. Methods: This is a randomized phase II trial of lymphodepleting chemotherapy followed by autologous TILs ± DC vaccine and high dose Interleukin-2 (IL-2) for patients with metastatic melanoma. Patients were randomized to receive TIL alone or TIL + DCs pulsed with MART-1 peptide. The primary objective was to determine whether patients receiving TIL + DCs have sustained persistence of infused T cells compared to patients treated with TIL alone. Secondary endpoints included evaluation of tumor response and survival. Results: A total of 18 patients with stage IV melanoma were treated; 89% with stage M1c, including 56% with brain metastasis; 17% had high LDH level. All but one patient were checkpoint naïve prior to TIL. Ten patients received TIL alone and eight received TIL + DC. Treatments were well tolerated with no grade 5 adverse events. There were no toxicities conferred by the DC vaccination. The ORR was 63% (5/8) in TIL + DC arm (1 CR, 4 PR) and 40% (4/10) in TIL arm alone (1 CR, 3 PR) (P=0.64). There was no statistically significant difference in survival between the arms. The median progression-free survival (PFS) was 3.6 months in the TIL arm and 7.2 months in the TIL+DC arm, while the median overall survival (OS) was 4.1 years in the TIL arm and 2 years in the TIL+DC arm. Tracking of the infused MART-1 reactive CD8+ T cells in the blood over time by flow cytometry showed no difference in persistence between the two arms. Conclusions: ACT with TILs has robust response in checkpoint naïve advanced melanoma patients. Despite numerically higher response rate in the TIL+DC arm, due to small patient number there was no statistically significant difference between the arms. Further testing of this approach in a prospective trial post-ICI is warranted. Trial Registration: All metastatic melanoma TIL lines were derived from tumor tissue obtained from patients enrolled on the TIL ACT clinical trial [institutional review board (IRB)-approved protocol# 2004-0069, NCT00338377 ] at The University of Texas MD Anderson Cancer Center. Ethics Approval: The United States Food and Drug Administration and the Institutional Review Board at MD Anderson Cancer Center approved the study. This study was conducted according to the principles from the Declaration of Helsinki. Consent: All study participants granted a written informed consent prior to treatment initiation. References: Rosenberg SA, Restifo NP. Adoptive cell transfer as personalized immunotherapy for human cancer. Science 2015;348(6230):62–8. Forget MA, Haymaker C, Hess KR, Meng YJ, Creasy C, Karpinets T, et al. Prospective Analysis of Adoptive TIL Therapy in Patients with Metastatic Melanoma: Response, Impact of Anti-CTLA4, and Biomarkers to Predict Clinical Outcome. Clin Cancer Res . 2018;24(18):4416–28. Banchereau J, Steinman RM. Dendritic cells and the control of immunity. Nature . 1998;392(6673):245–52.